Relevo discursivo e habilidade leitora no ensino médio - Moura, Maria Alvina Ferreira de (2024)
This research explores the cognitive concepts of figure and background, aiming to enhance critical reading skills among high school students within their literacy practices. The methodology is based on a qualitative approach, encompassing documentation, action based and collaborative researches. Initially, the documentation research involved selecting and analyzing activities from textbooks designed for different perceptual levels. Subsequently, the action research entailed the planning and implementation of a 12 class cycle for high schoolers, focusing on their critical reading of utilitarian texts (such as credit card bills, institutional advertisements, etc.), critical-humorous texts (such as cartoons), and journalistic texts (headlines, news articles, reports, etc.). The collaborative research involved the participation of the researcher and the Portuguese language school teacher, whose jointly implemented the classes and evaluative activities. The results revealed, mainly, that 1) attention plays a crucial role as a cognitive mechanism for perceiving and interpreting figure and background in a scene or text; 2) the figure and background categories are already included in basic education practices, through reading and analyzing text activities found in textbooks, even if not explicitly; 3) there are linguistic and non linguistic strategies to highlight or overshadow information in verbal and non-verbal texts; 4) the students' activities revealed that the research and action research contributed in some way to the development of the students' reading practices, when relating to applying focal adjustments. Researches of this nature contribute to innovate and upgrade teaching knowledge